Mechanical Probes Used on Uncooked Steaks Can Predict Cooked Beef Longissimus Tenderness - J. W. Stephens; J. A. Unruh; Michael E. Dikeman; M. C. Hunt; T. E. Lawrence; T. M. Loughin (Kansas Agricultural Experiment Station Research Reports, 2003)
We investigated five mechanical probes, used on uncooked strip loin steaks at 2 days postmortem, to predict trained sensory panel (TSP) tenderness and Warner-Bratzler shear force (WBSF) of steaks aged 14 days. Twenty-nine USDA Select strip loins were evaluated with sharp needle, blunt needle, sharp blade, and blunt blade probes in parallel and perpendicular orientations to the length of the strip loin. A steak from each loin was also measured with a plumb bob probe in a parallel orientation and with a Miniscan for instrumental color. None of the perpendicular orientation measurements were correlated (P>0.05) to TSP tenderness. The sharp blade and sharp needle probe values from the perpendicular orientation were correlated to WBSF (r=0.49 and 0.37, respectively). Parallel measurements by the sharp needle, blunt needle, sharp blade, blunt blade, and plumb bob probes were correlated with TSP tenderness (r=-0.77, - 0.40, -0.52, -0.57, and -0.53, respectively) and WBSF (r=0.74, 0.38, 0.60, 0.41, and 0.46). Instrumental color variables were not correlated (P>0.05) with TSP tenderness or WBSF. A regression equation for predicting TSP tenderness using the sharp needle probe resulted in R2 of 0.74, while the equation predicting TSP tenderness from WBSF had an R2 of 0.69. Equations using the sharp blade and plumb bob probe values in addition to L* values resulted in R2 values of 0.45 and 0.56, respectively. The sharp needle, sharp blade, and plumb bob probes were successful in predicting trained sensory panel tenderness. However, the sharp needle probe was superior to the other mechanical probes.
Keywords: beef cattle